Effect of super absorbent polymer on drought mitigation, and enhancing productivity and profitability of Indian mustard (Brassica juncea L.): DROUGHT MITIGATION IN MUSTARD THROUGH POLYMER - A K LANGADI; R L CHOUDHARY; R S JAT; H V SINGH; M L DOTANIYA; M K MEENA; O P PREMI; P K RAI (Journal of Oilseeds Research, 2021)
Under the current scenario of increasing demand of edible oil and dwindling irrigation water supply, the development of drought mitigation strategies is the need of the hour to increase productivity and profitability of the Indian mustard (Brassica juncea L.). A field experiment was conducted to evaluate the field efficacy of the superabsorbent polymer (SAP: Pusa hydrogel) and its application rates 0, 1.5, 2.5 and 5.0 kg/ha under moisture stress and normal moisture conditions in a factorial randomized complete block design and replicated thrice. The SCMR, dry matter accumulation, 1000-seed weight, oil and biological yields, economic indicators of the Indian mustard and also the soil available N, P and S contents were reduced (p = 0.05) under moisture stress regime, but improved considerably with the use of SAP. Across the moisture regimes, the maximum oil yield (1.12 t/ha), biological yield (9.24 t/ha), harvest index (29.12 %), gross returns (` 116140/ha), net returns (` 74790/ha), B: C ratio (1.81) and economic efficiency (` 519.4/ha/day) were recorded with SAP @ 5.0 kg/ha. SAP @ 2.5 to 5.0 kg/ha improved oil yield and net returns by 3 % (0.04 t//ha) and 2 % (` 1980/ha), respectively under normal moisture regime, while under moisture stress these parameters were increased by 13% (0.12 t/ha) and 14% (` 8280/ha), respectively. Further, under moisture stress, the maximum B:C ratio (1.66) was recorded with 5.0 kg SAP/ha, while it was the maximum(2.05) with 2.5 kg SAP/ha under the normal moisture regime. Across the moisture regimes, SAP @ 5.0 kg/ha, being on par with 2.5 kg SAP/ha improved the soil organic carbon, available N, P, K and S by 29.27, 13.61, 14.10, 11.95 and 25.01%, respectively over the control. Thus, 5.0 kg SAP/ha under moisture stress and 2.5 kgSAP/ha under normal moisture condition can be recommended for increasing yield, profit, savingwater and better soil health in Indian mustard.